Neuropsychiatric Lyme Disease and Vagus Nerve Stimulation - Nicholas Biniaz-Harris; Mara Kuvaldina; Brian A. Fallon (MDPI AG, 2023)
Lyme disease, the most common tick-borne disease in the United States, is caused by infection with the spirochete Borrelia burgdorferi. While most patients with acute Lyme disease recover completely if treated with antibiotics shortly after the onset of infection, approximately 10-30% experience post-treatment symptoms and 5-10% have residual symptoms with functional impairment (post-treatment Lyme disease syndrome or PTLDS). These patients typically experience pain, cognitive problems, and/or fatigue. This narrative review provides a broad overview of Lyme disease, focusing on neuropsychiatric manifestations and persistent symptoms. While the etiology of persistent symptoms remains incompletely understood, potential explanations include persistent infection, altered neural activation, and immune dysregulation. Widely recognized is that new treatment options are needed for people who have symptoms that persist despite prior antibiotic therapy. After a brief discussion of treatment approaches, the article focuses on vagus nerve stimulation (VNS), a neuromodulation approach that is FDA-approved for depression, epilepsy, and headache syndromes and has been reported to be helpful for other diseases characterized by inflammation and neural dysregulation. Transcutaneous VNS stimulates the external branch of the vagus nerve, is minimally invasive, and is well-tolerated in other conditions with few side effects. If well-controlled double-blinded studies demonstrate that transcutaneous auricular VNS helps patients with chronic syndromes such as persistent symptoms after Lyme disease, taVNS will be a welcome addition to the treatment options for these patients.